Analysis of the Potential for Improvement of Chemical‐Energy Transformation Processes. Issue 6 (2nd May 2017) - Adametz, Patrick; Baumgärtner, Andrea; Kohler, Tobias; Obermeier, Jonas; Siebert, Daniel; Müller, Karsten
Abstract: Much research aims to improve the efficiency of energy processes. However, it is often not clear where the biggest potential for improvement lies. Crucial for a namable improvement is a realistic chance for advancing the respective element as well as a significant influence of the respective element on the overall performance. A study on the potential for improving the efficiency of five exemplary chemical‐energy systems is presented. It was found that replacing working substances by alternatives with better enthalpies of reactions or solubility behavior carries huge potential for improving energy processes. However, in most cases there is little potential, for example, in lower heat capacity, even though heat capacity highly influences the efficiency of the processes. Abstract : Optimization potentials of processes are limited by two aspects: the dependency of efficiency on the different parameters and the domain of values of the parameters. A study on the determination of the parameters with the highest potential has been carried out for different energy processes.